1978
DOI: 10.1093/ajcn/31.1.134
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of available dietary iron

Abstract: Dietary iron requirements are dependent on the amount and availability of food iron ingested. On the basis of recent studies of food iron absorption employing extrinsic tag techniques, the availability of heme iron has been defined and estimates of the availability of nonheme iron based on the amounts of enhancing substances appear possible. A model has been developed whereby the availability of iron in a given meal may be estimated. Calculations are made on a meal basis of 1) the amount of heme iron and its a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
287
6
28

Year Published

1985
1985
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 525 publications
(330 citation statements)
references
References 26 publications
9
287
6
28
Order By: Relevance
“…It has been shown that physiological adaptation occurs after blood loss at delivery with an increase in iron absorption in postpartum women. Iron status of an individual is the main factor affecting iron absorption (Monsen et al, 1978). Absorption increases as iron stores become depleted and decreases as stores increase (Herbert, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that physiological adaptation occurs after blood loss at delivery with an increase in iron absorption in postpartum women. Iron status of an individual is the main factor affecting iron absorption (Monsen et al, 1978). Absorption increases as iron stores become depleted and decreases as stores increase (Herbert, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Haem Fe was assumed to constitute 40 % of total Fe (31) , including that in meat and fish. The remaining total Fe intake was assumed to be non-haem Fe.…”
Section: Dietary Assessmentmentioning
confidence: 99%
“…For non-haem iron, bioavailability was determined for each meal using an algorithm based on Monsen et al (1978) and modified by Murphy et al (1992). Starting with a basal percentage bioavailability of 5%, bioavailability was increased by the meal content of meat=fish=poultry protein (>9 g=4.18 MJ, þ5%; >27 g=4.18 MJ, þ10%) and ascorbic acid (>35 mg=4.18 MJ, þ5%; >105 mg=4.18 MJ, þ10%), and decreased by tannin-containing teas and coffees (250 g standard strength beverage, 720% of percentage bioavailability, to a maximum of 60% per meal).…”
Section: Determination Of Nutrient Intakes From Complementary Foodsmentioning
confidence: 99%